Pengaruh Perendaman Kawat Nikel-Titanium Termal Ortodonti dalam Minuman Teh Kemasan terhadap Gaya Defleksi Kawat (The Effect of Immersion Thermal Nickel-Titanium Archwire in The Bottled Tea Drinks to The Archwire Force Deflection) - Halimatus Sa'diyah Hasyim; Leliana Sandra Devi; Agus Sumono (Pustaka Kesehatan, 2016)
Background: The acidic salivary pH cause potentially undergo orthodontic wire constituent metal ions release. The release of metal ions can affect the quality of orthodontic wire.Objective: To analyze the effect of immersion thermal NiTi archwire in the bottled tea drinks to the archwire force deflection.Material andMethods: The sample size were 12 round thermal NiTi orthodontic archwires (3M; 0,016 inch) which divided into three groups: a control group (artificial saliva), a group of bottled tea drinks and bottled tea drinks of fruit flavors. The samples were immersed in an incubator for 10.5 hours at 37 ° C. The deflection test used Three-Point Bending method with a Universal Testing Machine in each group.Results and Conclusion: The results of One Way ANOVA test obtained value of 0.768 (p>0.05) which indicates that no significant difference in each group. The conclusion from this study is the bottled tea drinks can not affect the force deflection of thermal NiTi orthodontic archwires. Keywords: Bottled tea drinks, Force deflection, NiTi thermal archwire